Pengaruh Temperatur Mesin Terhadap Kadar Emisi NOx pada Motor dengan Bahan Bakar Compressed Natural Gas (CNG) - Hadi Rahmad; Mujahid Wahyu; Devina Rosa Hendarti (Polinema Press, Politeknik Negeri Malang, 2020)
The increase in NOx levels produced by CNG-fueled engines occurs when the fuel switches from gasoline to gas fuel (CNG). The author changed the otto 4 stroke gasoline engine, into a CNG-fueled motorbike and provided additional cooling in the form of a burst of air to the cylinder block. Changes in engine block temperature are detected using a temperature sensor placed on the engine oil. Bursts of air cooling result in temperature changes in engine oil. Changes in engine oil temperature are accompanied by changes in the resulting NOx emissions. This study shows that with a decrease in engine oil temperature in the combustion engine, NOx emission levels also decrease. From the research results it can be ignored that by providing additional air bursts will be able to reduce NOx emissions by up to 18%